Altered mapping of sound frequency to cochlear place in ears with endolymphatic hydrops provide insight into the pitch anomaly of diplacusis - J. J. Guinan (Nature Portfolio, 2021)
Abstract A fundamental property of mammalian hearing is the conversion of sound pressure into a frequency-specific place of maximum vibration along the cochlear length, thereby creating a tonotopic map. The tonotopic map makes possible systematic frequency tuning across auditory-nerve fibers, which enables the brain to use pitch to separate sounds from different environmental sources and process the speech and music that connects us to people and the world. Sometimes a tone has a different pitch in the left and right ears, a perceptual anomaly known as diplacusis. Diplacusis has been attributed to a change in the cochlear frequency-place map, but the hypothesized abnormal cochlear map has never been demonstrated. Here we assess cochlear frequency-place maps in guinea-pig ears with experimentally-induced endolymphatic hydrops, a hallmark of Ménière’s disease. Our findings are consistent with the hypothesis that diplacusis is due to an altered cochlear map. Map changes can lead to altered pitch, but the size of the pitch change is also affected by neural synchrony. Our data show that the cochlear frequency-place map is not fixed but can be altered by endolymphatic hydrops. Map changes should be considered in assessing hearing pathologies and treatments.